Gender Perception of Elementary School Students - Ramadhani, Amalia Nur (Al-Mudarris, 2025)
Gender is one of the issues that is often debated. Everyone certainly has different views regarding gender, especially among elementary school students. This article was written with the aim of describing the level of gender perception of elementary school students. Understanding of gender must be given as early as possible to avoid gender inequality. This study was conducted using a survey method conducted in two elementary schools in Purbalingga City, Central Java. The population of this study was 125 students. The sample used was a 100% saturated sample of the population. The results of the study showed a high level of gender perception of respondents at 67.2%. This means that respondents do not fully understand that men and women have the right and freedom to carry out activities according to their needs regardless of differences or social constructions in society. So, the higher the level of gender perception of respondents, the more they understand that there is no difference in the roles of men and women. Thus, more efforts are needed to improve understanding of gender equality.